Modes of Occurrences and Geochemical Characteristics of Ilmenite and Magnetite of the North Suoi Cun Lherzolite and Gabbroid - Hoa, Tran Trong; Svetliskaya, Tatiana; Izokh, Andrey; Nevolko, Petr; Anh, Tran Tuan; Shelepaev, R.; Phuong, Ngo Thi; Dung, Pham Thi; Can, Pham Ngoc; Ly, Vu Hoang (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 4, 2017)
Modes of occurrences and geochemical characteristics of ilmenite and magnetite in the North Suoi Cun ultramafic rocks were studied to understand source, formation and evolution of magma chamber. The northern Suoi Cun ultramafic block consists of plagiolherzolite and olivine melano-gabbro. The Plagiolherzolite and olivine melano-gabbro consist of large amounts of olivine and pyroxene, while lesser amounts of plagioclase and sulfit minerals and small amounts of biotite, chromspinel, ilmenite and magnetite were found. The results suggest that: a/ There are two types of ilmenite formed in two distinct stages: Early Mg-rich ilmenite was formed at intermediate magma chamber and latter Mn-rich ilmenite was formed at crystallized magma chamber; b/ Original magma of Suoi Cun plagiolherzolite and melano gabbroid was derived from sub-continental lithospheric mantle; c/ magnetite was formed at latter stage by two processes: serpentinization and alteration of early sulfit minerals. Keywords Ilmenite, magnetite, lherzolite, gabbroid, Suối Củn References [1] A.E. Izokh, G.V. Polyakov, Tran Trong Hoa, P.A. Balykin, Ngo Thi Phuong, Permian-Triassic ultramafic-mafic magmatism of Northern Vietnam and Southern China as expression of plume magmatism, Russian Geology and Geophysics, 46 (2005) 942. [2] A.I. Glotov, G.V. Polyakov, Tran Trong Hoa, Ngo Thi Phuong, A.E. Izokh, S.V. Kovyazin, P.A. Balykin, Hoang Huu Thanh, Bui An Nien, Pham Thi Dung, The late Permian Cao Bang PGE-Cu-Ni-bearing complex of the Song Hien structure, Northeastern Vietnam, Vietnam Journal of Geology, 23 B (2004.) 89. [3] D.I. Groves, S.E. Ho, N.M.S.Rock, M.E. Barley, M.T. Muggeridge, Archean cratons, diamond and platinum: evidence for coupled long-lived crust-mantle systems, Geology, 15 (1987) 801. [4] E.A. Mathez, Sulfide relations in Hole 418A flows and sulfur contents of glasses - Initial Reports of the DeepSea Drilling Project, U.S. Gov’t Printing Office, Washington, 53 (1979) 1069. [5] G.V. Polyakov, P.A. Balykin, A.E. Izokh, V.A. Aminsev, Ngo Thi Phuong, Tran Trong Hoa, Hoang Huu Thanh, Bui An Nien, Vu Van Van, Tran Quoc Hung, Hoang Viet Hang, Tran Tuan Anh, The mineralogy of Platinum group elements (PGE) in Permian - Triassic mafic-ultramafic associations of North Vietnam, Proceeding of the International Symposium: “Geology of Southeast Asia and adjacent areas, Ha Noi, (1995) 406. [6] G.V. Polyakov, Nguyễn Trọng Yêm (Đồng chủ biên), P.A. Balykin, Trần Trọng Hòa, Hoàng Hữu Thành, Trần Quốc Hùng, Ngô Thị Phượng, T.E. Petrova, Vũ Văn Vấn, Bùi Ấn Niên, Trần Tuấn Anh, Hoàng Việt Hằng, Các thành tạo mafic-siêu mafic Permi-Triat miền Bắc Việt Nam, NXB KH&KT, Hà Nội, 1996. [7] Ю.С. Геншафт, В.А. Цельмович, А.К. Гапеев, Г.М. Солодовников, Значение Fe-Ti оксидных минералов в науках о Земле, Вестник ОГГГН РАН, 1 (1999) 3. [8] Чан Чонг Хоа, Внутриплитный магматизм Северного Вьетнама и его металлогения: Диссертация на соискание ученой степени доктора геолого-минералогических наук. Институт Геологий и Минералогии, СО РАН, Новосибирск, 2007. [9] Tran Trong Hoa, A.E. Izokh, G.V. Polyakov, A.S. Borisenko, Ngo Thi Phuong, P.A. Balykin, Tran Tuan Anh, S.N. Rudnev, Vu Van Van, Bui An Nien, Permo-Triassic magmatism and metallogeny of North Vietnam in relation to Emeishan’s Plume, Russian Geology and Geophysics, 49 (2008) 480. [10] Trong-Hoa Tran, G.V. Polyakov, Tuan-Anh Tran, A.S. Borisenko, A. E. Izokh, P.A. Balykin, Thi-Phuong Ngo, Thi-Dung Pham, Intraplate Magmatism and Metallogeny of North Vietnam, Modern Approaches in Solid Earth Sciences, V.11, Springer, 2016. [11] J.M. Ade-Hall, L.K. Fink, H.P. Johnson, Petrography of opaque minerals, in R.S. Yeats, S.R. Hart, Initial Reports of Deep Sea Drilling Project, U.S. Government Printing Office, Washington, 34 (1976) 349. [12] J.J. Ague, G.H. Brimhall, Regional variations in bulk chemistry, mineralogy, and the compositions of mafic and accessory minerals in the batholiths of California, Geological Society of America Bulletin, 100 (1988) 891. [13] P.A. Balykin, Hoang Huu Thanh, Tran Quoc Hung, Tran Trong Hoa, Ngo Thi Phuong, Petrological peridotite-gabbroid’s types and their distribution in structures of North Vietnam, Vietnam Journal of Geology, 5-6 B (1995) 429. [14] П.А. Балыкин, Г.В. Поляков, Т.Е. Петрова, Р.А. Шелепаев, Чан Чонг Хоа, Нго Тхи Фыонг, Хоанг Хыу Тхань, Чан Куок Хунг, Составы исходных расплавов пермо-триассовых и триассово-юрских ультрамафит-мафитовых комплексов северного Вьетнама. Доклады РАН, 378 (2001) 225. [15] П.А. Балыкин, Г.В. Поляков, Чан Чонг Хоа, А.В. Лавренчук, А.Э. Изох, Нго Тхи Фыонг, А.И. Глотов, Хоанг Хыу Тхань, Т.Е. Петрова, Е.А. Васюкова, Состав и условия формирования позднепермского платиноидно-медь-никеленосного лерцолит-габбронорит-долеритового комплекса Каобанг (Северо-Восточный Вьетнам), Геология и геофизика, 47 (2006) 825. [16] S.J. Barnes, Chromite in komatiites: II. Modification during greenschist to mid-amphibolite facies metamorphism, Journal of Petrology, 41 (2000) 387. [17] T.B. Светлицкая, Состав и условия формирования рудной минерализации массива суойкун (Северо-восточный Вьетнам). Диссертация на соискание учёной степеникандидата геолого-минералогических наук. Институт Геологий и Минералогии, СО РАН, Hовосибирск, 2012. [18] T.V. Svetliskaya, P.A. Nevolko, Thi Phuong Ngo, Trong Hoa Tran, A.E. Izokh, R.A. Shelepaev, An Nien Bui, Hoang Ly Vu, Small- intrusion - hosted Ni-Cu-PGE sulphide deposits in northeastern Vietnam: Perspectives for regional mineral potential, Ore Geology Reviews, 86 (2017) 615. [19] Trần Văn Trị, Vũ Khúc (chủ biên), Địa chất và Tài nguyên Việt Nam (Chuyên khảo nhiều tác giả), NXB Khoa học Tự nhiên và Công nghệ, Hà Nội, 2010. [20] Э.Г. Конников, А.А. Цыганков, Д.А. Орсоев, Чайское медно-никелевое месторождение - Месторождения Забайкалья, Под ред. Н.П. Лаверова. – М.: Геоинформмарк, 1 (1995) 3947. [21] Г.В. Поляков, Чан Чонг Хоа, В.А. Акимцев, П.А. Балыкин, Нго Тхи Фыонг, Хоанг Хыу Тхань, Чан Куок Хунг, Буй Ан Ньен, Н.Д. Толстых, А.И. Глотов, Т.Е. Петрова, Ву Ван Ван, Рудно-геохимическая специализация пермотрмассовых ультрамафит – мафитовых комплексов Северного Вьетнама. Геология и Геофизика, 40 (1999), 1474.